2018
DOI: 10.1093/jrr/rry096
|View full text |Cite
|
Sign up to set email alerts
|

Clustered DNA double-strand break formation and the repair pathway following heavy-ion irradiation

Abstract: Photons, such as X- or γ-rays, induce DNA damage (distributed throughout the nucleus) as a result of low-density energy deposition. In contrast, particle irradiation with high linear energy transfer (LET) deposits high-density energy along the particle track. High-LET heavy-ion irradiation generates a greater number and more complex critical chromosomal aberrations, such as dicentrics and translocations, compared with X-ray or γ irradiation. In addition, the formation of >1000 bp deletions, which is rarely obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 53 publications
2
49
0
1
Order By: Relevance
“…In vivo studies have also shown that exposure to radiation can trigger carcinogenesis in subsequent generations. To date, numerous studies have shown that charged particle radiation is able to induce chromosomal aberrations and genomic instability in irradiated cells as well as their progenies [28,29,30]. Induction of mutation by heavy charged particles has been revealed by several studies [31,32].…”
Section: Genomic Instability Of Heavy Charged Particlesmentioning
confidence: 99%
“…In vivo studies have also shown that exposure to radiation can trigger carcinogenesis in subsequent generations. To date, numerous studies have shown that charged particle radiation is able to induce chromosomal aberrations and genomic instability in irradiated cells as well as their progenies [28,29,30]. Induction of mutation by heavy charged particles has been revealed by several studies [31,32].…”
Section: Genomic Instability Of Heavy Charged Particlesmentioning
confidence: 99%
“…The ionization density in particle tracks is usually characterized by a physical parameter called Linear Energy Transfer (LET) describing the average energy (in keV) given up by a charged particle traversing a distance of 1 μm. High-Z charged particles (such as Fe ions) are high LET particles that will produce dense ionizations along their path while photons (like X-rays) which produce sparse ionizations are considered as low LET IR ( Joiner and van der Kogel, 2018 ; Hagiwara et al, 2019 ). Although a same dose of radiation leads to the same amount of ionizations, the differences in their spatial distribution is translated into different types of damages at biological level.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because the scale of clustered DNA damage is in the order of 10-30 bp, i.e., <3-4 nm, whereas the scale of chromosomal rearrangements is in the order of >1000 bp, i.e., >50-100 nm distance. To explain this discrepancy between clustered DNA lesions and chromosomal rearrangements in terms of scale, the possibility of mis-rejoining two DSBs belonging to distinct loci must be considered [39]. Indeed, this difference may be resolved by the existence of clustered DSBs in close proximity along the tracks of high-LET particle radiation.…”
Section: Can Clustered Dna Lesions Alone Account For the Formation Ofmentioning
confidence: 99%